2015
DOI: 10.1007/s11695-015-1644-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of FTO and Vitamin D for the Weight Loss Effect of Roux-en-Y Gastric Bypass Surgery in Obese Patients

Abstract: BackgroundA recent study in children demonstrated that the rs9939609 single-nucleotide polymorphism in the fat mass and obesity (FTO) gene influences prospective weight gain, however, only in those who were vitamin D-deficient. If this might also be the case for Roux-en-Y gastric bypass (RYGB), surgery-induced weight loss is however unknown. The objective of this study is to examine if the magnitude of RYGB surgery-induced weight loss after 2 years depends on patients’ FTO rs9939609 genotype (i.e., TT, AT, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…These were divided into categories according to the type of the surgical procedure and the dose range of vitamin D supplementation. Only eight studies showed a mean 25(OH)D level > 30 ng/ml at 6 to 24 months post operatively [51,52,60,66,69,73,75,80]. Thirteen studies showed a mean 25(OH)D level < 20 ng/ml at 6 months to 11 years post operatively [51,54,55,64,78,8592].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These were divided into categories according to the type of the surgical procedure and the dose range of vitamin D supplementation. Only eight studies showed a mean 25(OH)D level > 30 ng/ml at 6 to 24 months post operatively [51,52,60,66,69,73,75,80]. Thirteen studies showed a mean 25(OH)D level < 20 ng/ml at 6 months to 11 years post operatively [51,54,55,64,78,8592].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, studies administering a maintenance vitamin D supplementation of 400–2,000 IU daily, and additional doses to deficient and/or insufficient individuals (additional equivalent dose range 1,100 IU–7,100 IU, total daily dose received 1,500–9,100 IU), with the exception of Fish et al [69], consistently demonstrated an increase in mean 25(OH)D level of 9–13 ng/ml at six months [59] (Appendix), and at one year post operatively (Figure 3) [52,60,62,66,73,75]. The mean baseline 25(OH)D level in this group of studies was 13–25 ng/ml.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FTO risk allele carriers lose less weight than common allele homozygous individuals after banding surgery [222,223], but experience a similar level or more weight reduction after gastric bypass surgery [222,224].…”
Section: Obesity-predisposing Gene Variants Interact With Bariatric Smentioning
confidence: 99%